Ethanolic extract of black soldier fly (Hermetia illucens L.) larvae for wound healing in mice (Mus musculus L.) - Sandakila, Darman; Hadi, Gracetia D.; Gultom, Riska; Samalele, Seni; Nugroho, Rudy A. (Aceh Journal of Animal Science, 2024)
The Black Soldier Fly (Hermetia illucens L.) or BSF is one of a group of insects that has a length of 15-20 mm originating from America. The larvae of the BSF has a high protein content (44.26%), which has great potential in treating wound healing. This study investigated the wound healing potential of Black Soldier Fly Larvae (BSFL) ethanolic extract on mice. The research aimed to determine the extract's content, its effect on wound closure percentage, and its impact on total DNA content in mice. Using a completely randomized design, 30 male mice were divided into 6 treatment groups: no treatment (K-1), placebo (K-2), povidone iodine 10% (K+), and BSFL ethanolic extract at 10%, 15%, and 20% concentrations. Wounds were treated for 14 days, with measurements taken every 2 days. Results showed that the 20% BSFL extract was most effective in wound healing, with wound lengths comparable to the povidone iodine group. The highest total DNA content was observed in the 20% BSFL group (42.25 7.45 g/mL), indicating enhanced cell proliferation. Gas Chromatography Mass Spectrophotometry analysis revealed high lauric acid content (44.27%) in the extract, known for its antibacterial properties. Organoleptic and homogeneity tests confirmed the ointment's suitability for topical application. The extract's efficacy is attributed to its high protein content, various amino acids, and minerals that play crucial roles in wound healing processes. The study concludes that BSFL ethanolic extract, particularly at 20% concentration, shows promising potential as a natural wound healing agent, offering antibacterial and tissue regeneration properties. These findings open new avenues for developing sustainable, insect-based wound healing treatments.